Role of the Social Support and Health Status in Living Arrangement Preference of the Elderly in China—A Cross-Sectional Study - Cui, Longyan; Li, Jingshan; Xie, Danni; Wang, Minghui; He, Fanrong; Chen, Junfeng; Ding, Ding (Frontiers in Public Health, 2022)
Background: Living arrangements of the elderly are one of the most important components that affect their quality of life in later years. The aging, with the phenomenon of low fertility rate and family structure transformation, has caused changes in the living arrangements of the elderly. This research is to find the tendency of living arrangement preferences of the elderly and the influencing factors. Methods: This study obtained data from The Chinese Longitudinal Healthy Longevity Survey (CLHLS) database. Elderly people who are ≥60 years old in the 2018 survey cohort were included. Chi-square test and binary logistic regression were used to analyze the living arrangement preferences and influencing factors. Results: Currently, in terms of the preference of the elderly in living arrangements, nearly half (45.6%) choose not to live with their children. The binary model results showed that married (OR=0.166, 95%CI: 0.147-0.187), 6 years and above education (OR=0.600, 95%CI: 0.517-0.695), ADL disabled (OR=0.810, 95%CI:0.720-0.912), multiple chronic diseases (OR=0.803, 95%CI:0.720-0.912) and obtained social services (OR=0.884, 95%CI:0.803-0.972) incline to not live with their children. The elderly who living in rural (OR=1.244, 95%CI:1.129-1.371), with an income of more than 500,000 yuan(OR=1.557,95%CI:1.380-1.757), with children visiting (OR=1.405,95%CI:1.161-1.707) and children’s financial support (OR=1.194, 95%CI:1.080-1.319) are more likely to choose to live with their children. Conclusions: Traditional living with children is no longer the only option for the elderly. The elderly care services provided by communities or professional care institutions may be the mainstream way of taking care of the elderly citizens in the aging society. Improving the types and forms of community nursing services to increase the accessibility of these services; setting up elderly care institutions reasonably and equipping adequate professional nursing staff should be considered as priority measures.